Transcriptional trajectories of anther development provide candidates for engineering male fertility in sorghum - Namrata Dhaka (Nature Portfolio, 2020)
Abstract Sorghum is a self-pollinated crop with multiple economic uses as cereal, forage, and biofuel feedstock. Hybrid breeding is a cornerstone for sorghum improvement strategies that currently relies on cytoplasmic male sterile lines. To engineer genic male sterility, it is imperative to examine the genetic components regulating anther/pollen development in sorghum. To this end, we have performed transcriptomic analysis from three temporal stages of developing anthers that correspond to meiotic, microspore and mature pollen stages. A total of 5286 genes were differentially regulated among the three anther stages with 890 of them exhibiting anther-preferential expression. Differentially expressed genes could be clubbed into seven distinct developmental trajectories using K-means clustering. Pathway mapping revealed that genes involved in cell cycle, DNA repair, regulation of transcription, brassinosteroid and auxin biosynthesis/signalling exhibit peak expression in meiotic anthers, while those regulating abiotic stress, carbohydrate metabolism, and transport were enriched in microspore stage. Conversely, genes associated with protein degradation, post-translational modifications, cell wall biosynthesis/modifications, abscisic acid, ethylene, cytokinin and jasmonic acid biosynthesis/signalling were highly expressed in mature pollen stage. High concurrence in transcriptional dynamics and cis-regulatory elements of differentially expressed genes in rice and sorghum confirmed conserved developmental pathways regulating anther development across species. Comprehensive literature survey in conjunction with orthology analysis and anther-preferential accumulation enabled shortlisting of 21 prospective candidates for in-depth characterization and engineering male fertility in sorghum.